Beauty Myths in Disney’s Short Film “Reflect”: A Semiotic Analysis (PANOPTICON: Journal of English Studies, 2024)
The portrayal of female beauty in media often establishes rigid standards that influence societal perceptions of ideal physical characteristics. Women who do not conform to these ideals are frequently marginalized and treated unfairly. This research aims to explore the myth of the ideal female body as depicted in Disney's short film Reflect. Utilizing qualitative research and Roland Barthes' semiotic analysis, the study examines how beauty myths shape societal expectations. The findings reveal that societal standards of beauty—typically white, tall, and slim—are perpetuated through media representations. The film's protagonist strives to challenge these norms and redefine beauty standards within the ballet world.